Behavioural and morphological traits influence sex‐specific floral resource use by hummingbirds. Issue 11 (29th May 2022) - Maglianesi, María A.; Maruyama, Pietro K.; Temeles, Ethan J.; Schleuning, Matthias; Zanata, Thais B.; Sazima, Marlies; Gutiérrez‐Zamora, Aquiles; Marín‐Gómez, Oscar H.; Rosero‐Lasprilla, Liliana; Ramírez‐Burbano, Mónica B.; Ruffini, Alejandra E.; Salamanca‐Reyes, J. Ricardo; et al.
Abstract: Research on resource partitioning in plant–pollinator mutualistic systems is mainly concentrated at the levels of species and communities, whereas differences between males and females are typically ignored. Nevertheless, pollinators often show large sexual differences in behaviour and morphology, which may lead to sex‐specific patterns of resource use with the potential to differentially affect plant reproduction and diversification. We investigated variation in behavioural and morphological traits between sexes of hummingbird species as potential mechanisms underlying sex‐specific flower resource use in ecological communities. To do so, we compiled a dataset of plant–hummingbird interactions based on pollen loads for 31 hummingbird species from 13 localities across the Americas, complemented by data on territorial behaviour (territorial or non‐territorial) and morphological traits (bill length, bill curvature, wing length and body mass). We assessed the extent of intersexual differences in niche breadth and niche overlap in floral resource use across hummingbird species. Then, we tested whether floral niche breadth and overlap between sexes are associated with sexual dimorphism in behavioural or morphological traits of hummingbird species while accounting for evolutionary relatedness among the species. We found striking differences in patterns of floral resource use between sex. Females had a broader floral niche breadth and were more dissimilar in the plant species visited with respect to males of the same species, resulting in a high level of resource partitioning between sexes. We found that both territoriality and morphological traits were related to sex‐specific resource use by hummingbird species. Notably, niche overlap between sexes was greater for territorial than non‐territorial species, and moreover, niche overlap was negatively associated with sexual dimorphism in bill curvature across hummingbird species. These results reveal the importance of behavioural and morphological traits of hummingbird species in sex‐specific resource use and that resource partitioning by sex is likely to be an important mechanism to reduce intersexual competition in hummingbirds. These findings highlight the need for better understanding the putative role of intersexual variation in shaping patterns of interactions and plant reproduction in ecological communities. Abstract : Research on resource partitioning in plant–pollinator mutualistic systems is mainly concentrated at the levels of species and communities, whereas differences between males and females are typically ignored. Discover why behaviour and morphology are important factors influencing sex‐specific patterns in resource use in hummingbird species across the Americas. Photo: Cauã Galeazzi de Menezes. Resumen: La investigación sobre la partición de recursos en los sistemas mutualistas planta‐polinizador se concentra principalmente en los niveles de especies y comunidades, mientras que las diferencias entre machos y hembras suelen ser ignoradas. Sin embargo, los polinizadores suelen mostrar grandes diferencias sexuales en su comportamiento y morfología, lo que puede dar lugar a patrones específicos de uso de recursos para cada sexo con el potencial de afectar de forma diferencial la reproducción y la diversificación de las plantas. Se estudió la variación en los rasgos de comportamiento y morfológicos entre sexos de las especies de colibríes como posibles mecanismos que explican el uso de recursos florales específicos para cada sexo en las comunidades ecológicas. Para ello, se recopiló un conjunto de datos de interacciones planta‐colibrí con base en las cargas de polen de 31 especies de colibríes de 13 localidades en las Américas, además de datos sobre su comportamiento territorial (territorial o no territorial) y rasgos morfológicos (longitud y curvatura del pico, longitud del ala y masa corporal). Se evaluaron las diferencias intersexuales en la amplitud y el solapamiento del nicho en el uso de los recursos florales para las distintas especies de colibríes. Posteriormente, se comprobó si la amplitud del nicho floral y el solapamiento entre sexos están asociados con el dimorfismo sexual en los rasgos de comportamiento o morfológicos de las especies de colibríes, teniendo en cuenta el parentesco evolutivo entre las especies. Se encontraron diferencias notables en los patrones de uso de los recursos florales entre sexos. Las hembras presentaron una mayor amplitud de nicho floral y fueron más disímiles en las especies de plantas visitadas con respecto a los machos de la misma especie, lo que resultó en un alto nivel de partición de recursos entre los sexos. Se encontró que tanto la territorialidad como los rasgos morfológicos están relacionados con el uso de recursos específicos por sexo en las especies de colibríes. En particular, el solapamiento de nicho entre sexos fue mayor para las especies territoriales que para las no territoriales y, además, el solapamiento de nicho se asoció negativamente con el dimorfismo sexual en la curvatura del pico en las especies de colibríes. Estos resultados revelan la importancia de los rasgos conductuales y morfológicos de las especies de colibríes en el uso de recursos según el sexo y que la partición de recursos entre sexos es probablemente un mecanismo importante para reducir la competencia intersexual en los colibríes. Estos resultados ponen de manifiesto la necesidad de comprender mejor el rol que tiene la variación intersexual en los patrones de interacción y en la reproducción de las plantas en las comunidades ecológicas.